Sosialisasi Tata Kelola Destinasi Pariwisata Dan Pemanfaatan Media Digital Di Desa Wisata Kedisan Kabupaten Gianyar - Ida Bagus Gede Agung Widana; I Wayan Mertha; Luh Yusni Wiarti; Ni Putu Oka Agustini; Anom Hery Suasapha; Dyah Cynthia Putri (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
This article reports the community engagement program organized by the Tourism Destination Study Program of Bali Tourism Polytechnic. The program was held in Kedisan Tourism Village of Tegalalang District in Gianyar Regency, on June 26th, 2022, in the form of socialization. The event was prepared carefully through a situation analysis based on data collected through field observations and interviews with Kedisan Village officials.  The topics presented in the socialization consisted of tourism village governance and digital media for marketing tourism village products.  The community engagement activities have been carried out well in providing an understanding of the importance of implementing tourism village governance, especially for Kedisan Village which has been legalized as a tourist village. In addition, the event raised awareness about the importance of utilizing digital media to market Kedisan Tourism Village's products. Evaluation based on the participant's perceptions shows that the community engagement satisfied all the participants. The evaluation also succeeded in formulating things that are hoped to be achieved by the residents of Kedisan Village through the next community engagement of the Tourism Destination Study Program.